علاقة الكفاءة الذاتية الأكاديمية بالتوافق النفسي لدى طلبة الصفوف من 7-12 في سلطنة عمان - الجهورية، فاطمة بنت سعيد; الظفري، سعيد بن سليمان (جامعة السلطان قابوس, 2018)
This study investigated the relationship between academic self-efficacy and psychological adjustment among 2821 students (grades 7 to 12) who were selected from all Omani school districts. It also aimed at exploring the predictive possibility of academic self-efficacy by psychological adjustment, and identifying the differences in academic self-efficacy and psychological adjustment according to gender and age. Two scales of academic self-efficacy and psychological adjustment were applied in order to obtain study data, after verifying their validity and reliability. The results showed statistically significant differences due to gender and class in both academic self-efficacy and psychological adjustment. Moreover, results of the multiple regression analysis showed that the adaptive adjustment subscale was the only significant predictor of academic self-efficacy and contributed with a percentage of (15.2%) in explaining the difference in students' scores in the academic self-efficacy scale.
هدفت الدراسة الحالية لفحص علاقة الكفاءة الذاتية الأكاديمية بالتوافق النفسي لدى عينة من طلبة الصفوف (ن= 2821) طالبا وطالبة من طلبة الصفو ف السابع وحتى الثاني عشر (7-12) والذين تم اختيارهم من عينة من المدارس التابعة لجميع المناط ق التعليمية في سلطنة عمان. كما سعت الدراسة لاستكشاف إمكانية التنبؤ بالكفاءة الذاتية الأكاديمية من خلال التوافق النفسي، ولتحديد الفروق في الكفاءة الذاتية الأكاديمية والتوافق النفسي تبعا لمتغيري الجنس والصف. ولغايات جمع بيانات الدراسة، تم تطبيق مقياس الكفاءة الذاتية الأكاديمية ومقياس التوافق النفسي بعد التأكد من صدقها وثباتها. وأشارت النتائج إلى وجود فروق ذات دلالة إحصائية في مستوى الكفاءة الذاتية الأكاديمية والتوافق النفسي تعزى لمتغير الجنس لصالح الإناث، ولوجود فروق دالة إحصائيا في مستوى الكفاءة الذاتية الأكاديمية تعزى لمتغير الصف ولصالح الصف التاسع والعاشر، وفي مستوى التوافق لصالح الصف الثاني عشر، وأظهرت نتائج تحليل الانحدار الخطي المتعدد أن بعد التوافق الإيجابي هو المتنبئ الدال الوحيد وأسهم بنسبة (15.2%) في تفسير التباين في درجات الطلبة على مقياس الكفاءة الذاتية الأكاديمية.
Keywords: التعليم الأساسي; سلطنة عمان; التوافق النفسي; الكفاءة الذاتية الأكاديمية